Pengetahuan dan Perilaku Penggunaan Antibiotik pada Masyarakat Kabupaten Karawang: Studi Cross Sectional - Tuti Wiyati; Hana Fadhilah Sutrisno; Nurhasnah Nurhasnah (Journal of Islamic Pharmacy, 2025)
Antibiotics are drugs used to kill or inhibit the growth of microbes, and their use should be under medical supervision. The rapid development of digital information and limited access to certain healthcare services have led to a persistent phenomenon: the habitual use of antibiotics without medical prescription. This study aims to investigate the relationship between public knowledge and behavior regarding antibiotic use in West Karawang District, Karawang Regency. This observational study employed a cross-sectional design conducted from February to May 2024. A total of 400 respondents who met the inclusion criteria from 8 urban villages in West Karawang participated in this study. Data were analyzed descriptively using frequency distribution tables and further analyzed using the Spearman’s Rho test to determine the correlation between knowledge and behavior in antibiotic use. The results showed that the majority of respondents were female (58.0%), aged 46–60 years (34.3%), and had a high school education as their highest educational attainment (54.3%). Based on the knowledge categorization, 65.8% of the respondents had a good level of knowledge regarding antibiotic use, and 56.3% of the population in West Karawang District demonstrated good behavior in antibiotic use. The Spearman’s Rho test showed a significant relationship between the level of knowledge and behavior in antibiotic use (p 0.05), with a correlation coefficient of 0.407. In conclusion, the community in West Karawang District possesses good knowledge and behavior regarding antibiotic use. The better an individual's knowledge, the more rational their use of antibiotics tends to be.Keywords: Antibiotic, Knowledge, Behaviour of Using Antibiotic